CRISPR FokI Dead Cas9 System: Principles and Applications in Genome Engineering - Maryam Saifaldeen; Dana E. Al-Ansari; Dindial Ramotar; Mustapha Aouida (Cells, 2020)
The identification of the robust clustered regularly interspersed short palindromic repeats (CRISPR) associated endonuclease (Cas9) system gene-editing tool has opened up a wide range of potential therapeutic applications that were restricted by more complex tools, including zinc finger nucleases (ZFNs) and transcription activator-like effector nucleases (TALENs). Nevertheless, the high frequency of CRISPR system off-target activity still limits its applications, and, thus, advanced strategies for highly specific CRISPR/Cas9-mediated genome editing are continuously under development including CRISPR–FokI dead Cas9 (fdCas9). fdCas9 system is derived from linking a FokI endonuclease catalytic domain to an inactive Cas9 protein and requires a pair of guide sgRNAs that bind to the sense and antisense strands of the DNA in a protospacer adjacent motif (PAM)-out orientation, with a defined spacer sequence range around the target site. The dimerization of FokI domains generates DNA double-strand breaks, which activates the DNA repair machinery and results in genomic edit. So far, all the engineered fdCas9 variants have shown promising gene-editing activities in human cells when compared to other platforms. Herein, we review the advantages of all published variants of fdCas9 and their current applications in genome engineering.